2017
DOI: 10.3390/ijms18071587
|View full text |Cite
|
Sign up to set email alerts
|

Human Chorionic Gonadotropin and Breast Cancer

Abstract: Breast cancer is well known as a malignancy being strongly influenced by female steroids. Pregnancy is a protective factor against breast cancer. Human chorionic gonadotropin (HCG) is a candidate hormone which could mediate this antitumoral effect of pregnancy. For this review article, all original research articles on the role of HCG in breast cancer were considered, which are listed in PubMed database and were written in English. The role of HCG in breast cancer seems to be a paradox. Placental heterodimeric… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 104 publications
0
27
0
1
Order By: Relevance
“…Early studies by Russo and others suggested that human placental hormone chorionic gonadotropin (hCG) provided an inhibitory action, leading to reduction in breast cancer risk, as reviewed in reference [ 54 ]. This long-lasting protective effect could also be reproduced by administering placental hCG to rats for 21 days [ 28 ].…”
Section: Female Hormones Pregnancy and Prevention Of Breast Cancmentioning
confidence: 99%
See 3 more Smart Citations
“…Early studies by Russo and others suggested that human placental hormone chorionic gonadotropin (hCG) provided an inhibitory action, leading to reduction in breast cancer risk, as reviewed in reference [ 54 ]. This long-lasting protective effect could also be reproduced by administering placental hCG to rats for 21 days [ 28 ].…”
Section: Female Hormones Pregnancy and Prevention Of Breast Cancmentioning
confidence: 99%
“…This long-lasting protective effect could also be reproduced by administering placental hCG to rats for 21 days [ 28 ]. The mechanism proposed suggested placental hCG was responsible for imprinting the permanent changes in the genomic signature of the mammary gland [ 54 ]. These changes occurred within a time window of pregnancy rendering the cells refractory to malignant transformation [ 54 ].…”
Section: Female Hormones Pregnancy and Prevention Of Breast Cancmentioning
confidence: 99%
See 2 more Smart Citations
“…Breast cancer, together with lung and colorectal cancers, accounts for 46% of all cancer-related deaths in women and nearly half a million women die each year from this disease [1] [2]. It is a cancer type that still has the highest mortality rate among women, after lung cancer, in spite of a certain improvement in survival rates since the 1990s.…”
Section: Introductionmentioning
confidence: 99%